Scrotal hemangioma: a case report and systematic literature review - Chang, Zhe; Man, Jiangwei; Wang, Jirong; Gui, Huiming; Niu, Jiping; Yang, Li (Frontiers in Oncology, 2025)
PurposeThis study aimed to provide a case of scrotal hemangioma and examine its characteristics.MethodsWe presented a case report involving a sixteen-year-old male, detailing symptoms, physical examination, imaging studies, diagnosis, and treatment. We conducted a thorough literature analysis of case reports and examined their clinical characteristics, pathological categorization, recurrence, and complications.ResultsOur study comprised 21 patients with scrotal hemangioma. The average age was 27.14 years, with a range from 21 days to 84 years. 57.1% of the hemangiomas affected the organs. 61.9% of patients were situated on the right side of the scrotum. Ninety percent of patients experienced no pain. Merely 33.3% of patients exhibited additional symptoms, which encompassed azoospermia, hemorrhage, calcification, hydrocele, thrombosis, and ulceration. The predominant pathological classification was cavernous scrotal hemangioma, representing 38.1% of the cases. All patients received surgical resection, and the majority experienced neither relapse nor postoperative complications.ConclusionsScrotal hemangioma, an uncommon benign neoplasm in adolescents, frequently remains asymptomatic but may disrupt fertility and, in rare instances, lead to severe problems. Timely identification, diagnosis, and surgical intervention are essential for good patient outcomes.